Alaska, the Last Frontier of Privacy: Using the State Constitution to Eliminate Pretextual Traffic Stops - Kaban, Jeffrey M. (2004)
The Alaska Supreme Court has consistently interpreted its state constitution to provide a greater right to privacy than the United States Supreme Court. In United States v. Whren, the United States Supreme Court upheld the practice of pretextual traffic stops, thereby permitting police officers to use traffic violations as a pretext to investigate crime in the absence of probable cause. However, the Alaska Supreme Courts has issued no clear ruling as to whether state case law finding pretextual stops unconstitutional remains controlling. As a result of Alaska's failure to directly address this issue, the state's lower courts are divided as to whether to apply Whren's objective standard or current state case law's subjective standard to determine whether a stop is pretextual. This Note, which examines the concurrent development of legal rulings on pretextual traffic stops in Alaskan and the United States Supreme Court, focuses on Alaska state constitutional jurisprudence. More specifically, it explores Alaska search and seizure and vehicular stop jurisprudence to demonstrate the greater expectation of vehicular privacy that Alaska affords citizens. Lastly, this Note argues that Alaska should adopt a two-part test involving subjective and objective elements to determine whether a stop is pretextual